2016
DOI: 10.1249/01.mss.0000485227.10860.75
|View full text |Cite
|
Sign up to set email alerts
|

The Completeness Of Intervention Descriptions In Randomised Trials Of Supervised Exercise Training In Peripheral Arterial Disease

Abstract: Research supports the use of supervised exercise training as a primary therapy for improving the functional status of people with peripheral arterial disease (PAD). Several reviews have focused on reporting the outcomes of exercise interventions, but none have critically examined the quality of intervention reporting. Adequate reporting of the exercise protocols used in randomised controlled trials (RCTs) is central to interpreting study findings and translating effective interventions into practice. The purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Poor reporting impacts on the ability to translate empirical findings into clinical practice and ultimately impacts the potential benefit to patients [1,24,28]. Our analysis found the reporting quality of key intervention components to be poor and insufficient to allow for their replication regardless of whether TIDieR [1,18,30,37] or CERT guidelines [6,22] were applied. None of the original studies provided complete information for all essential intervention elements, making accurate replication of the included interventions more difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor reporting impacts on the ability to translate empirical findings into clinical practice and ultimately impacts the potential benefit to patients [1,24,28]. Our analysis found the reporting quality of key intervention components to be poor and insufficient to allow for their replication regardless of whether TIDieR [1,18,30,37] or CERT guidelines [6,22] were applied. None of the original studies provided complete information for all essential intervention elements, making accurate replication of the included interventions more difficult.…”
Section: Discussionmentioning
confidence: 99%
“…However, this does represent an improvement in comparison with the previous studies (33-74 %). As far as we are aware, the only other evaluations of the reporting quality of exercise trials within cardiovascular research are based on the TIDieR framework and have been carried out for cardiac rehabilitation [1] and peripheral arterial disease (PAD) trials [30]. These studies demonstrated similar or even more frequent missing information on F.I.T.T.…”
Section: Comparison With Other Studies Reporting On the Description Omentioning
confidence: 99%
“…Exercise interventions, in other populations, such as cardiac rehabilitation60 and peripheral arterial disease,61 also demonstrate poor reporting (when assessed according to the TIDieR criteria). This highlights that incomplete reporting of exercise interventions is not isolated to PFP, but also a problem in relation to exercise for other non-musculoskeletal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In one review, only 39% of the non-pharmacological trials provided complete data for the intervention details (14). In a review of supervised exercise training in people with peripheral arterial disease, only around one-quarter of the trials described complete data for the mode of exercise, intensity of exercise, and tailoring/progression; and around one-tenth reported exercise intensity comprehensively (22). Similar findings were found on exercise-based cardiac rehabilitation trials (23).…”
Section: Introductionmentioning
confidence: 91%
“…Authors of RCTs are encouraged to use the TIDieR checklist for reporting the interventions in enough detail to enable replication and facilitate the potential impact of their research on both health and society (29). The TIDieR checklist was used to rate the completeness of reporting of the intervention in the formal analyses cited above (22) (23).…”
Section: Introductionmentioning
confidence: 99%